Interleukin (IL)‐39 [IL‐23p19/Epstein–Barr virus‐induced 3 (Ebi3)] induces differentiation/expansion of neutrophils in lupus‐prone mice. (12th August 2016) - Wang, X.; Liu, X.; Zhang, Y.; Wang, Z.; Zhu, G.; Han, G.; Chen, G.; Hou, C.; Wang, T.; Ma, N.; Shen, B.; Li, Y.; et al.
Summary: Interleukin (IL)‐12 family cytokines play critical roles in autoimmune diseases. Our previous study has shown that IL‐23p19 and Epstein–Barr virus‐induced 3 (Ebi3) form a new IL‐12 family heterodimer, IL‐23p19/Ebi3, termed IL‐39, and knock‐down of p19 or Ebi3 reduced diseases by transferred GL7 + B cells in lupus‐prone mice. In the present study, we explore further the possible effect of IL‐39 on murine lupus. We found that IL‐39 in vitro and in vivo induces differentiation and/or expansion of neutrophils. GL7 + B cells up‐regulated neutrophils by secreting IL‐39, whereas IL‐39‐deficient GL7 + B cells lost the capacity to up‐regulate neutrophils in lupus‐prone mice and homozygous CD19 cre (CD19‐deficient) mice. Finally, we found that IL‐39‐induced neutrophils had a positive feedback on IL‐39 expression in activated B cells by secreting B cell activation factor (BAFF). Taken together, our results suggest that IL‐39 induces differentiation and/or expansion of neutrophils in lupus‐prone mice.